Wenlock (Silurian) graptolites, Cape Phillips Formation, Canadian Arctic Islands - Lenz, A. C.; Melchin, M. J. (Transactions of the Royal Society of Edinburgh: Earth Sciences, 1991)
Twenty six of the more important species of monograptids (s.l.), retiolitids and Cyrtograptus (from a total fauna of 52 species) are described from Wenlock strata of the Cape Phillips Formation, Canadian Arctic Archipelago. Of this fauna, eight new species or subspecies, Monograptus firmus festinolatus, M. instrenuus, M. opimus, M. testis incomptus, Cyrtograptus falcatus, C. hamatus brevis, C. kolobus and C. pseudomancki , are described and illustrated. Wenlock biostratigraphic zones comprise the Cyrtograptus centrifugus-C. insectus Zone (earliest Wenlock), M. instrenuus-C. kolobus Zone, tentatively divisible into lower and upper subzones, C. perneri-M. opimus Zone possibly divisible into lower and upper subzones, C. lundgreni-M. testis Zone divisible into a lower M. testis incomptus Subzone and an upper M. testis testis Subzone, and the Pristiograptus ludensis Zone (latest Wenlock).